MWCNTs functionalization and immobilization with anti-Brucella antibody; towards the development of a nanosensor. (December 2017) - Wahab, Rizwan; Khan, Shams T.; Ahmad, Javed; Ansari, S.G.; Musarrat, Javed; Al-Khedhairy, Abdulaziz A.
Abstract: Brucellosis is endemic worldwide due to the nomadic heritage of drinking fresh milk from goats, sheeps and camels. This study aims at developing an antibody based sensor for the detection of Brucella, wherein the binding of Brucella to the sensor will be detected by measuring the changes in electrical signals via cyclic voltammetric properties. The morphology of the used MWCNTs was observed under SEM, FESEM, and TEM. The MWCNTs (ropes like structure) used for the development of sensor were 2–4 μm in length and ∼10–15 nm in diameter as observed under SEM, FESEM, and TEM. MWCNTs were functionalized via acid treatment/oxidation process and the functional behavior of molecules was confirmed with FTIR spectroscopy. Antibodies were conjugated onto the functionalized MWCNTs using classical EDC coupling reactions. When observed under SEM, binding of Brucella abortus to these anti- Brucella antibody functionalized MWCNTs was clearly observed. Finally, these antibody functionalized MWCNTs were deposited on aluminum sheets for the voltammetric detection of Brucella . Results indicate that the antibody functionalized MWCNTs prepared in this study can be used successfully for the detection of Brucella . Highlights: The Brucellosis disease is prevalent due to consumption of fresh milk from goats, sheep and camels. The ropes of MWCNTs were functionalized and antibodies were conjugated via EDC coupling reactions. The binding of Brucella abortus to antibodies modified MWCNTs were observed via SEM. The antibody functionalized MWCNTs were utilized for the detection of Brucella abortus. The functionalized CNTs were conjugates with anti- Brucella antibody analyzed by CV.